A Descriptive Qualitative Summary Analysis of an Important Correlation among Factors in Textbook Selection - Aprilla, Kresensia (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2024)
Selecting the proper textbook to be used during the teaching-learning process is a quite complicated process. The selection process is taken not only by teachers but also by other possible people, for instance the government or the curriculum committee of the education institution. Therefore, whoever finalize the decision on choosing the textbook, then its selection process must acquire the fit or the balance correlation between the textbooks and these three factors: the students, the teachers, and the curriculum. In this paper, the author will focus on describing the important correlation between these three factors with the textbook during the textbook selection process. Shortly, this descriptive qualitative analysis summary article may also help the teachers or the educators, especially, to give full attention to these factors to select the perfect textbooks to be used as the sources during the teaching-learning processes. In addition, it is also hoped that the students will be eased and have a better understanding of the lesson material and the source of information when the teachers succeed in selecting the textbooks by keeping these three factors in mind.Selecting the proper textbook to be used during the teaching-learning process is a quite complicated process. The selection process is taken not only by teachers but also by other possible people, for instance the government or the curriculum committee of the education institution. Therefore, whoever finalize the decision on choosing the textbook, then its selection process must acquire the fit or the balance correlation between the textbooks and these three factors: the students, the teachers, and the curriculum. In this paper, the author will focus on describing the important correlation between these three factors with the textbook during the textbook selection process. Shortly, this descriptive qualitative analysis summary article may also help the teachers or the educators, especially, to give full attention to these factors to select the perfect textbooks to be used as the sources during the teaching-learning processes. In addition, it is also hoped that the students will be eased and have a better understanding of the lesson material and the source of information when the teachers succeed in selecting the textbooks by keeping these three factors in mind.